Media, development and democracy - Pait, Heloisa; Laet, Juliana (Studies in media and communications, 2021)
Sponsored by the Communication, Information Technologies, and Media Sociology section of the American Sociological Association (CITAMS), this book explores the complex construction of democratic public dialogue in developing countries. Case studies examine national environments defined not only by state censorship and commercial pressure, but also language differences, international influence, social divisions, and distinct value systems. With fresh portraits of new and traditional media throughout Africa, Latin America and Asia, authors delve into the essential role of the media in developing countries. Case studies illuminate the relationship between the State and the media in Russia, as well as the challenges faced by journalists working in Kurdistan. Further cases reveal bureaucratic censorship of books in Brazil, regulatory dilemmas in Australia, state policies in post-colonial Malawi, and the potential of oral culture for the strengthening of democratic conversation. Media, Development and Democracy brings the liberal democratic media model into new terrains where some of its core assumptions do not hold. In doing so, the authors' collective voices illuminate pressing issues facing our current global dialogue and our liberal and democratic expectations concerning communications and the media. This essential volume works as a magnifying glass for our current times, forcing us to question what kind of media we want today.